Trans abdominal Ultrasonography in Acute Pancreatitis: a cross sectional study - Gyawali, Merina; Shrestha, Ashish; Sharma, Prakash; Shrestha, Binod Bade; Bhattarai, Subash (Nepal Mediciti Medical Journal, 2021)
BACKGROUND: Acute pancreatitis (AP) is a common cause of acute pain abdomen. Contrast-enhanced Computed Tomography (CECT) of the abdomen is the imaging method of choice in acute pancreatitis. Ultrasonography can be used as the first, easily available imaging modality for the assessment of the pancreas. This study aims to study the transabdominal USG findings in patients with acute pancreatitis. It will also compare USG findings with CT findings in acute pancreatitis. METHODS: A hospital-based cross-sectional, prospective study comprising of consecutive 55 patients with acute pancreatitis was conducted over a study period of 15 months. Trans abdominal USG findings and CECT abdominal findings in acute pancreatitis were studied and compared. Data analysis was done using SPSS version 20 and a p-value of ≤0.05 was considered significant. RESULTS: Pancreas was visualized by USG in only 69%. Ultrasonography had some pancreatic and/or extrapancreatic findings in patients with acute pancreatitis in 84.2% of patients in whom the pancreas was visualized, whereas, it was 98.2% by CECT abdomen. USG was unable to demonstrate findings in 75% of patients with mild acute pancreatitis. CONCLUSION: Transabdominal ultrasonography detection of pancreatitis was inferior to the CECT. It had a limited role in detecting mild acute pancreatic cases. Nonetheless, detection of etiological factor such as gallstones, and assessment of extra pancreatic fluid collection like ascites and pleural effusion were better visualised with ultrasound. USG is readily available, cheap, noninvasive, and can be utilized as an initial diagnostic tool for acute pancreatitis and ruling out other causes of acute abdomen.